Challenges of breastfeeding in Haitian women in Chile - Velásquez-Muñoz, Andrea (2024)
Objective: To identify the knowledge and practices regarding breastfeeding among Haitian women hospitalized in the postpartum period at the Hospital San Juan De Dios in Santiago, Chile. Material and methods: Descriptive cross-sectional study with a sample of 45 Haitian postpartum women between March and December 2019. Data were collected using a structured questionnaire validated by experts and translated into Creole. Descriptive statistics were used to analyze the data. Results: 90% of the surveyed women have general knowledge about breastfeeding, although only 30% can identify at least two specific benefits. 80% believe that exclusive breastfeeding should last at least six months. Most women (60%) think that complementary foods should be introduced after six months. There is no association between sociodemographic variables and the level of knowledge. Conclusions: The findings highlight the need for educational programs that address cultural and linguistic barriers to improve breastfeeding rates in this population.